Plasma cell neoplasia after kidney transplantation: French cohort series and review of the literature - Kormann, Raphaël; François, Hélène; Moles, Thibault; Dantal, Jacques; Kamar, Nassim; Moreau, Karine; Bachelet, Thomas; Heng, Anne-Elisabeth; Garstka, Antoine; Colosio, Charlotte; Ducloux, Didier; Sayegh, Johnny; et al. (PloS one, 2017)
Although post-transplant lymphoproliferative disorder (PTLD) is the second most common type of cancer in kidney transplantation (KT), plasma cell neoplasia (PCN) occurs only rarely after KT, and little is known about its characteristics and evolution. We included twenty-two cases of post-transplant PCN occurring between 1991 and 2013. These included 12 symptomatic multiple myeloma, eight indolent myeloma and two plasmacytomas. The median age at diagnosis was 56.5 years and the median onset after transplantation was 66.7 months (2-252). Four of the eight indolent myelomas evolved into symptomatic myeloma after a median time of 33 months (6-72). PCN-related kidney graft dysfunction was observed in nine patients, including six cast nephropathies, two light chain deposition disease and one amyloidosis. Serum creatinine was higher at the time of PCN diagnosis than before, increasing from 135.7 (±71.6) to 195.9 (±123.7) μmol/l (p = 0.008). Following transplantation, the annual rate of bacterial infections was significantly higher after the diagnosis of PCN, increasing from 0.16 (±0.37) to 1.09 (±1.30) (p = 0.0005). No difference was found regarding viral infections before and after PCN. Acute rejection risk was decreased after the diagnosis of PCN (36% before versus 0% after, p = 0.004), suggesting a decreased allogeneic response. Thirteen patients (59%) died, including twelve directly related to the hematologic disease. Median graft and patient survival was 31.7 and 49.4 months, respectively. PCN after KT occurs in younger patients compared to the general population, shares the same clinical characteristics, but is associated with frequent bacterial infections and relapses of the hematologic disease that severely impact the survival of grafts and patients.